MODAL SOSIAL, KEWIRAUSAHAAN PEREMPUAN, DAN KEBERLANJUTAN UMKM DI INDONESIA: ANALISIS BIBLIOMETRIK DAN SYSTEMATIC LITERATURE REVIEW - Salma Rivani Luawo (LPPM Universitas Negeri Surabaya, 2025)
The study maps the scientific development of social capital, women’s entrepreneurship, and MSME sustainability in Indonesia through a bibliometric analysis and systematic literature review derived from the original document’s content. The research identifies publication trends, thematic structures, and collaboration networks shaping the national knowledge system. The analysis shows that social capital plays a strategic role in strengthening women entrepreneurs’ capabilities through networks, trust, collective norms, and community support. The study finds that women face structural barriers such as limited access to finance, low digital literacy, and weak formal networks. Social capital enhances business resilience through bonding, bridging, and linking mechanisms that reduce transaction costs, expand market opportunities, and increase adaptive capacity. The bibliometric findings indicate significant growth in research interest after the COVID-19 pandemic and highlight three dominant clusters: social capital, women entrepreneurs, and MSME performance. The SLR results confirm that social capital directly influences women-owned MSMEs’ performance and acts as a mediator between women’s empowerment and business sustainability. The study proposes a theoretical model integrating perspectives from Bourdieu, Coleman, and Putnam to explain relational dynamics shaping women’s economic behavior. The research contributes to applied social science theory and offers practical recommendations for women’s empowerment policies built on strengthened social networks.